Context and Intonation in the Perception of Sarcasm. - Woodland, Jennifer; Voyer, Daniel (Metaphor & Symbol, 2011)
This experiment investigated the relative contribution of context and tone of voice in the perception of sarcasm in short utterances. Eighty-two participants heard short stories read in a monotone voice reflecting either a positive or a negative context, followed by a relevant statement in a sarcastic or sincere tone of voice. Context and tone of voice were either congruent (e.g., positive context with sincere tone) or incongruent (e.g., positive context with sarcastic tone). Participants were asked to rate from 1 to 7 whether they perceived the statement as very sincere (1) or very sarcastic (7). Results indicated a significant context by tone interaction on both ratings and response time. Specifically, mid-range ratings and longer reaction times were obtained when context and tone were incongruent compared to when they were congruent. The discussion emphasizes the interplay of context and tone of voice in the perception of a sarcastic statement.